La alimentaciòn y su incidencia en la Salud Integral de los/las Adolecentes. - JImènez Balcazar, Andrea Elizabeh (2015)
The present work research with title "THE FOOD AND HIS INCIDENCE IN THE INTEGRAL HEALTH OF THE TEENAGERS” made in Educational Unit “Ovidio Decroly and Eliseo Arias Carrión” of the city Catamayo province of Loja, it was based on specific objectives that allowed “Promoting adequate food in the adolescents in the 8th years basic general education, enhancing Holistic Health through a proposal of Social Intervention.” The specific objectives, allowed to establish actions that facilitated to identify theories on the subject of food, which led to know causes and consequences ok inadequate nutrition for Health and handle the issue better, to establish intervention strategies and providing alternatives actual diagnosis solution. The methodology used was part of the characteristics of a scientific, historical, inductive, deductive, descriptive and statistical study process that served to explain and provide alternative solutions to the research, using research tools such as observation sheet and the survey of: faculty, parents and students of the eighth year parallel a and B that are legally registered and attending classes normally. The main findings from field research, events suggest that poor diet has negative effects on health and the overall development of students, where the 5 main causes stem from lack of knowledge and direction of parents on adequate nutrition in their homes, it's little oversight and control in schools regarding the sale of foods that students need daily adds, the most consumed foods in excess simple carbohydrates and saturated fats, which cause damages in Health as weakness, anxiety, not motivate, overweight, and the limited development of adolescent physical and cognitive activities. Therefore it is important to keep energy balance of nutrients: cereals, proteins, fats, carbohydrates simple and complex; and substances such as minerals, vitamins, iron and zinc; accompanied of sport or exercise and performance of activities that encourage personal growth and development. The design of a Nutritious Food Guide Healthy and Balanced, which allows the school authorities promote healthy lifestyles and prevent diseases consequent inadequate nutrition: From these results a proposal for Social Intervention under activities as presented.